2020
DOI: 10.1002/1873-3468.13736
|View full text |Cite
|
Sign up to set email alerts
|

Divergent metabolic responses dictate vulnerability to NAMPT inhibition in ovarian cancer

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Piacente et al demonstrated that NAPRT-proficient ovarian and pancreatic cancers are resistant to FK866, whereas NAPRT downregulation through gene silencing or chemical inhibition with 2-hydroxynicotinic acid (2-HNA) sensitized tumor cells to NAMPT inhibitors both in vitro and in vivo [25]. In line with these results, another study highlighted that sensitivity to NAMPT inhibition in several ovar-ian cancer cell lines was inversely proportional to NAPRT expression [41]. Despite its usefulness in basic research as NAPRTi, the low molecular weight and high functionality of 2-hydroxynicotinic acid suggest that this compound could have non-specific effects.…”
Section: Introductionmentioning
confidence: 91%
“…Piacente et al demonstrated that NAPRT-proficient ovarian and pancreatic cancers are resistant to FK866, whereas NAPRT downregulation through gene silencing or chemical inhibition with 2-hydroxynicotinic acid (2-HNA) sensitized tumor cells to NAMPT inhibitors both in vitro and in vivo [25]. In line with these results, another study highlighted that sensitivity to NAMPT inhibition in several ovar-ian cancer cell lines was inversely proportional to NAPRT expression [41]. Despite its usefulness in basic research as NAPRTi, the low molecular weight and high functionality of 2-hydroxynicotinic acid suggest that this compound could have non-specific effects.…”
Section: Introductionmentioning
confidence: 91%
“…[7][8][9][10][11] Intriguingly, some cancer-type-specific metabolic activities show narrow requirements for a particular nutrient, which represents a unique vulnerability of that cancer to therapeutic targeting based on that nutrient. [12][13][14] It is clear that both tumor and non-tumor cells are influenced by the availability of nutrients in their microenvironment 15 (Figure 2).…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Intriguingly, some cancer-type-specific metabolic activities show narrow requirements for a particular nutrient, which represents a unique vulnerability of that cancer to therapeutic targeting based on that nutrient. [12][13][14] It is clear that both tumor and non-tumor cells are influenced by the availability of nutrients in their microenvironment 15 (Figure 2). In vivo, the concentrations of many circulating nutrients, which are synthesized de novo or absorbed due to dietary intake, are regulated systemically, although concentrations of some nutrients in the tumor interstitial fluid reportedly differ from those seem in plasma.…”
mentioning
confidence: 99%
“…The rate-limiting enzyme of this pathway, NAMPT, has been targeted in pre-clinical studies and in clinical trials for treatment of multiple cancers, with mixed results 29 , 30 . Recent studies using NAMPT inhibitors as monotherapy in ovarian cancer cell lines have shown promising results to overcome drug resistance in certain contexts 31 , 32 . We evaluated the inhibition of NAMPT using the small molecule daporinad 33 in four of our acquired resistance models (those with higher IC 50 values to olaparib) and observed little to no effect.…”
Section: Resultsmentioning
confidence: 99%
“…3 a). On the other hand, the inhibition of NAMPT prevents cancer cells from regenerating NAD+ from nicotinamide, thus drastically reducing the intracellular concentration of this coenzyme 32 . We confirmed that this is the case by quantifying NAD+ in OV1946or cells after 24 h of treatment and show that the relative NAD+ levels in daporinad-treated cells are significantly lower than in untreated controls.…”
Section: Resultsmentioning
confidence: 99%